The FOXE1 and NKX2-1 loci are associated with susceptibility to papillary thyroid carcinoma in the Japanese population. Issue 9 (5th July 2011) - Matsuse, Michiko; Takahashi, Meiko; Mitsutake, Norisato; Nishihara, Eijun; Hirokawa, Mitsuyoshi; Kawaguchi, Takahisa; Rogounovitch, Tatiana; Saenko, Vladimir; Bychkov, Andrey; Suzuki, Keiji; Matsuo, Keitaro; Tajima, Kazuo; et al.
Abstract : Background: FOXE1 and NKX2-1 are two known genetic risk factors for the predisposition to sporadic papillary thyroid carcinoma (PTC) in Europeans, but their association in other ethnicities is still unknown. Objective: We aim to examine the association of the two genes with Japanese sporadic PTC, which exhibits high BRAF V600E mutation rate. Methods: 507 Japanese sporadic PTC cases and 2766 controls were genotyped for rs965513 ( FOXE1 ) and rs944289 ( NKX2-1 ). PTC cases were also examined for their BRAF V600E mutational status. Results: The association of both rs965513 (p=1.27×10 −4, OR=1.69, 95% CI 1.29 to 2.21) and rs944289 (p=0.0121, OR=1.21, 95% CI 1.04 to 1.39) with the risk of sporadic PTC was confirmed. Subgroup analysis based on the BRAF mutational status showed strong association of rs965513 with BRAF V600E -positive cases (p=2.26×10 −4, OR=1.72, 95% CI 1.29 to 2.29), but not with BRAF V600E -negative cases (p=0.143, OR=1.52, 95% CI 0.87 to 2.65). However, there was no difference in the observed effect size between both subgroups. For rs944289, both subgroups showed marginal association (p=0.0585, OR=1.17, 95% CI 0.99 to 1.37 for BRAF V600E -positive cases; p=0.0492, OR=1.35, 95% CI 1.00 to 1.81 for BRAF V600E -negative cases). Conclusions: Both FOXE1 and NKX2-1 were associated with the increased risk of sporadic Japanese PTC. No clear associations were observed for either SNP with BRAF V600E status.